1981
DOI: 10.1111/j.1365-2923.1981.tb02418.x
|View full text |Cite
|
Sign up to set email alerts
|

A medical curriculum: evaluation by final-year students

Abstract: Seventy-five students, at the end of their final year, responded to a postal questionnaire designed to assess their views on their medical curriculum. The responses of those intending to enter general practice were compared with those of intending hospital doctors and comparison were also made between respondents who had enrolled for a 6-year course and those who had enrolled for the newer 5-year course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 6 publications
2
19
0
2
Order By: Relevance
“…A British investigation (Walker et al 1981) revealed the same trend but more strongly. Table 2 summarizes the data from medical students in the final year at Aberdeen University, showing the 10 subjects regarded as most essential to the training of doctors and the time allocated to each of these 10 subjects.…”
Section: Resultsmentioning
confidence: 63%
“…A British investigation (Walker et al 1981) revealed the same trend but more strongly. Table 2 summarizes the data from medical students in the final year at Aberdeen University, showing the 10 subjects regarded as most essential to the training of doctors and the time allocated to each of these 10 subjects.…”
Section: Resultsmentioning
confidence: 63%
“…Various studies report that students have difficulties putting their theoretical knowledge into clinical practice and recognise deficiencies in the required basic skills in medical activities [4]. A study was able to demonstrate that a quarter of the medical students reported having difficulties transferring pre-clinical basic knowledge into clinical work [5]. …”
Section: Introductionmentioning
confidence: 99%
“…L'attitude des étudiants en médecine face à l'apprentissage des TC a été explorée dans plusieurs études de la littéra-ture médicale 9,10 . Au Liban, cet apprentissage ne faisait pas partie, jusqu'à la date du présent travail, des programmes des facultés de médecine.…”
Section: Introductionunclassified